ANALISIS GOOD GOVERNANCE DALAM PERCEPATAN PEMBANGUNAN DESA - Mira Andriani; Ririn Yulianti; Anwar Musadad (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
Based on the researcher's initial observations, namely the concentration of physical development in the Banjar City government in Langensari District, the researcher was interested in conducting research on how good governance principles are applied in village development in Waringinsari Village, Langensari District, Banjar City. The researcher hopes that by implementing good governance principles, village development will prioritize physical and non-physical development in a balanced manner. This research employed a descriptive qualitative methodology. Purposive sampling, which involves selecting data sources based on specific considerations, was used to collect data through in-depth interviews with predetermined informants (Sugiyono, 2013: 53-54). The results indicate that the application of good governance principles to accelerate village development in Waringinsari Village, Langensari District, Banjar City has been quite successful. However, the principles of democracy and empowerment remain weak. It is recommended that the community be more involved in village deliberations, which will determine development priorities that align with the needs of the village community.